Hydroxychloroquine for COVID-19: a single center, retrospective cohort study - Wen, Chung Ho; Yong, Wei Xin; How, Kang Nien; Khalid, Khairil Erwan; Zulkifli, Shazwani; Idris, Salmah (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2022)
Introduction: The outbreak of coronavirus disease (COVID-19) in December 2019 called for a rapid solution, leading to repurposing of existing drugs. Due to its immunomodulatory effect and antiviral properties, hydroxychloroquine (HCQ) has been used in early 2020 for treatment of COVID-19 patients. This study was conducted to evaluate the treatment outcome of HCQ monotherapy in Malaysia. Methods: A retrospective cohort study was conducted in COVID-19 ward in Hospital Kuala Lumpur (HKL), from March to April 2020. A total of 446 COVID-19 patients were recruited, only 325 patients were finally included for analysis. Statistical analysis was done using SPSS, with a significant value set at p<0.05. Results: The mean age of the patients were 38.5 ±15.5. They were majority male, (n=210, 64.6%) Malaysian (n=239, 73.5%) and Malay ethnicity (n=204, 62.8%). Ninety-one (28%) patients received HCQ monotherapy. HCQ monotherapy was associated with worse outcome (OR: 10.29, 95% CI 1.17-90.80). There was a significant difference in mean length of stay between those with and without HCQ treatment (t323=5.868, p<0.001, 95% CI, 2.56-5.31). The average length of stay for HCQ treated group was 3.84 days longer than those without treatment. 6.6% of the patient receiving HCQ monotherapy encountered adverse drug effects. Conclusion: Similar to study reported worldwide, our study demonstrated that HCQ did not improve length of stay and the outcome of COVID-19 patients.